Setting It Right: Employment Protection, Labour Reallocation and Productivity - John P. Martin; Stefano Scarpetta (Institute for the Study of Labor (IZA), 2011)
This paper provides a critical review of the recent empirical evidence on the links between regulations affecting the hiring and firing of workers, labour reallocation and productivity growth. It also reviews how workers affected by labour mobility fare and discusses policy options to support them. The upshot is that employment protection has a sizeable effect on labour market flows and these flows, in turn, have significant impacts on productivity growth. At the same time, the evidence also shows that while greater labour market reallocation benefits many workers through higher real wages and better careers, some displaced workers lose out via longer unemployment durations and/or lower real wages in post-displacement jobs. In this context, reforms of employment protection should be considered as part of a comprehensive package that also includes an adequate safety net for the unemployed and effective re-employment services.
Keywords: J23; J53; K31; 330; job and worker flows; employment protection; productivity; Arbeitnehmerschutz; Arbeitsmobilität; Produktivität; Wirtschaftswachstum; Welt